Double burden of malnutrition among the mother-child pairs at household level in Nepal. - Shrestha, Nitesh. (Tufts University. Tisch Library., 2019)
This poster shows that double burden of malnutrition exists in mother-child pair at household level in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy